Electroimpedance Spectroscopy for the Measurement of the Dielectric Properties of Sodium Chloride Solutions at Different Glucose Concentrations - Stefano Sbrignadello; Andrea Tura; Paolo Ravazzani (Journal of Spectroscopy)
We investigated possible variations of impedance values in samples of sodium chloride solution (sodium chloride 0.9%) with glucose at different concentrations, ranging from 5000 to around 75 mg/dL. The sodium chloride solution (either saline physiological solution) was chosen since it has similarities to blood but no cell components, which may be confounding factors in this study. Special focus was on the effect of stirring and of temperature variations on the impedance spectrum of samples at different glucose concentrations. We found that variations in glucose concentration directly affect the impedance modulus of the sample both in static conditions and in dynamic conditions due to stirring, as well as at both room temperature and at increased temperature. In fact, even if the impedance variations were often small (around 3-4 mΩ per mg/dL), they were usually clearly measurable. These findings may be the basis for possible development of a new approach, based on impedance technology, for the noninvasive monitoring of glycaemia.